Psychometric Evaluation of Patient-reported Outcomes Measurement Information System Physical Function Computer Adaptive Testing in Minimally Invasive Lumbar Spine Surgery: An Analysis of Responsiveness, Coverage, Discriminant Validity, and Concurrent Validity. - Vaishnav, Avani S.; McAnany, Steven J.; Iyer, Sravisht; Albert, Todd J.; Gang, Catherine Himo; Qureshi, Sheeraz A. (Journal of the American Academy of Orthopaedic Surgeons, 2020)
Introduction: Although the Patient-reported Outcomes Measurement Information System (PROMIS) is increasingly being used, there are few studies assessing the psychometric properties of PROMIS in minimally invasive spine (MIS) surgery. Thus, the purpose of this study was to perform a psychometric evaluation of PROMIS Physical Function Computer Adaptive Testing (PROMIS-PF CAT) in MIS lumbar surgery.Methods: The patient-reported outcome measures collected preoperatively and postoperatively of patients undergoing MIS lumbar surgery were retrospectively analyzed to assess responsiveness, coverage, discriminant validity, and concurrent validity of PROMIS-PF CAT.Results: Four hundred twenty-one patients were included. The responsiveness of PROMIS Physical Function (PROMIS-PF) was lower than that of the Oswestry Disability Index (ODI) in the decompression subgroup. Although the ODI had a ceiling effect of 16.7% at 1 year, the Short-Form 12 physical health score and PROMIS-PF did not show floor or ceiling effects. PROMIS-PF demonstrated discriminant validity preoperatively and postoperatively and convergent validity with the ODI, as evidenced by a significant strong negative correlation but not with the Short-Form 12 Physical Health Score, as evidenced by the variability in strength of correlation.Conclusions: Although the PROMIS-PF showed lower responsiveness than the ODI, particularly in the decompression subgroup, it demonstrated discriminant validity preoperatively and postoperatively, convergent validity with ODI, and better coverage than ODI. These findings suggest that the PROMIS-PF CAT demonstrates reasonable psychometric properties and may be a good surrogate for the ODI.